Madrigals, Songs and Canons - Byrd, William 1539/40-1623; Brett, Philip (London Stainer & Bell New York Galaxy Music Corp., 1976)
Of madrigals and partsongs, Volume 16 of the Byrd Edition contains the six items not included in the printed sets of 1588, 1589 and 1611 (distinguished by the lack of obligatory instrumental accompaniments); of the consort songs, the original versions of consort songs that were subsequently arranged as madrigals; and of canons and rounds, the two that can without doubt be attributed to the composer.
edited from manuscript and printed sources
Keywords: 16th Century (1501-1600); Song; Madrigal; Canon